The impact of reputational risks on investment activity - Gutkevych, Svitlana; Sydorenko, Pavlo (My University, 2016)
Despite economic jitters and slow growth worldwide, international financial markets have been gradually rebounding from the global financial crisis of 2007-2008, driving investment and development. However, market imperfections, as well as a range of unfavourable fundamentals, may constrain the access of some countries,industries and firms to external financing, influencing their investment spending and growth.The dynamic business environment, information asymmetry, volatility of exogenousdeterminants and endogenous transformations contribute to the uncertainty and its impact on investment. Reputation of investment stakeholders provides valuable guidelines for the investment decisions under uncertainty, and proper management of reputational risks eliminates investors’ exposure to numerous related risks. However, available approaches to the evaluation and management of reputational capital and risks require further elaboration, incl. within the framework of investment development strategy of a country. The authors suggest the definition of both reputational capital and reputational risks, analyse the impact of reputational risks on investment activity, incl. the impact of sovereign reputational risks on the investment attractiveness and relevant flows.
Keywords: investment; reputational risks; sovereign defaults; reputational capital; attractiveness; кафедра міжнародної економіки; інвестиційна привабливість; інвестування; суверенні дефолти; репутаційні ризики; репутаційний капітал; инвестирование; инвестиционная привлекательность; репутационные риски; репутационный капитал; кафедра міжнародної економіки